2007
DOI: 10.1111/j.1479-8425.2006.00249.x
|View full text |Cite
|
Sign up to set email alerts
|

Does variation in workload affect fatigue in a regular 12-hour shift system?

Abstract: The aim of the current study was to examine the relationship between workload and objective/subjective fatigue for a regularly rotating work schedule. Twenty male shift-workers working a 12-h schedule at a metallurgic smelter were involved in the study. Data were collected for a 14-day period while the participants continued their work schedule and duties. Shifts with high and low workload were separated and compared. Trends were observed for the increase of fatigue with a higher workload. Subjective fatigue w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…However, several of our field studies have demonstrated that the PDA-PVT is also suitable for use in the field, when conditions are often less than ideal. To date, we have successfully used this device in several work environments, including international flight operations, long-haul train travel, and mining operations (Baulk et al, 2007;Jay, Dawson, & Lamond, 200;Lamond et al, 2006;Petrilli et al, 2006). It is also imp^t to note that although the PDA-PYT may provide anlindication of the fatigue levels associated with a roster, it is simply a sustained attention task, not a test of higher cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several of our field studies have demonstrated that the PDA-PVT is also suitable for use in the field, when conditions are often less than ideal. To date, we have successfully used this device in several work environments, including international flight operations, long-haul train travel, and mining operations (Baulk et al, 2007;Jay, Dawson, & Lamond, 200;Lamond et al, 2006;Petrilli et al, 2006). It is also imp^t to note that although the PDA-PYT may provide anlindication of the fatigue levels associated with a roster, it is simply a sustained attention task, not a test of higher cognitive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas the standard length of the PVT in laboratory studies has often been 10 min, field studies involving the PDA-PVT have typically used a 5-min version of the task, since it is more practical for environments with time constraints (Baulk et al, 2007;Kamimori, Johnson, Thorne, & Belenky, 2005;Killgore, Killgore, Ganesan, Krugler, & Kamimori, 2006;McLellan, Kamimori, Bell, et al, 2005;McLellan, Kamimori, Voss, et al, 2005;Petrilli, Roach, Daw-N. Lamond,1amo0026@flinders.eduau son, & Lamond, 2006).…”
mentioning
confidence: 99%
“…The focus of the current study was to evaluate sleep, fatigue and performance in smelter workers working a typical (DDNNOOOO), regular-rotating 12-h shift roster in order to determine the potential for disruption to the sleep-wake cycle, fatigue, reduced alertness and impaired performance as a result of extended work periods. This investigation formed part of a larger study to investigate several elements of 12-h shift schedules including the effects of workload and age on fatigue and performance (Baulk et al, 2007;Kandelaars et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Using a six point scale it provides a workload score for workplace activities [18]. Increasing workload scores for tasks where the only change is duration can indicate increasing workplace fatigue [3].…”
Section: Measurementsmentioning
confidence: 99%